Alcohol Electronic Screening and Brief Intervention: A Community Guide Systematic Review - Tansil, Kristin A. (Am J Prev Med, 2016)
CONTEXT: Excessive drinking is responsible for 1 in 10 deaths among working-age adults in the U.S. annually. Alcohol screening and brief intervention (ASBI) is an effective, but underutilized, intervention for reducing excessive drinking among adults. Electronic screening and brief intervention (e-SBI) uses electronic devices to deliver key elements of ASBI, and has the potential to expand population reach. EVIDENCE ACQUISITION: Using Community Guide methods, a systematic review of the scientific literature on the effectiveness of e-SBI for reducing excessive alcohol consumption and related harms was conducted. The search covered studies published from 1967 to October 2011. A total of 31 studies with 36 study arms met quality criteria, and were included in the review. Analyses were conducted in 2012. EVIDENCE SYNTHESIS: Twenty-four studies (28 study arms) provided results for excessive drinkers only and seven studies (eight study arms) reported results for all drinkers. Nearly all studies found that e-SBI reduced excessive alcohol consumption and related harms: nine study arms reported a median 23.9% reduction in binge drinking intensity (maximum drinks/binge episode) and nine study arms reported a median 16.5% reduction in binge drinking frequency. Reductions in drinking measures were sustained for up to 12 months. CONCLUSION: According to Community Guide rules of evidence, e-SBI is an effective method for reducing excessive alcohol consumption and related harms among intervention participants. Implementation of e-SBI could complement population-level strategies previously recommended by the Community Preventive Services Task Force for reducing excessive drinking (e.g., increasing alcohol taxes and regulating alcohol outlet density).